Communicating through cultural performances the lived experiences of the junior high school students in the community technical college of Southeastern Mindanao, Inc. - Revisa, Nicole T. (2018)
Historically, the lumad has experienced various kinds of harassments in their communities. In this study, the researcher looked into the cultural performance about the lived experiences of the junior high school students at the Community Technical College of Southeastern Mindanao, Inc., (CTCSM). The students presented three cultural performances titled Pahayagan, Naghaharing Uri, and Yutang Kabilin. To understand these performances, the researcher applied Keir Elam?s (1980) the semiotics of theatre and drama and his categorization of codes: proxemics, kinesics, and paralinguistic. In their performances, emerged their lived experiences of harassments, the military presence in their communities, and their desire to reclaim their ancestral land. Moreover, they also emphasized the importance of farming and their rich cultural background. The narratives of the students also showed that they call any activities that they are able to incorporate their culture to be a ?cultural performance?.